Ambient Intelligence European Conference, AmI 2014, Eindhoven, The Netherlands, November 11-13, 2014. Revised Selected Papers - Aarts, Emile; de Ruyter, Boris; Markopoulos, Panos; van Loenen, Evert; Wichert, Reiner; Schouten, Ben; Terken, Jacques; Van Kranenburg, Rob; Den Ouden, Elke; O'Hare, Gregory (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the refereed proceedings of the 5th International Joint Conference of Ambient Intelligence, AmI 2014, held in Eindhoven, The Netherlands, in November 2014. The 21 revised full papers presented together with 5 short papers and 4 workshop papers were carefully reviewed and selected from 59 submissions. The papers are organized along a set of thematic tracks: ambient assisted living; internet of things; ambient play and learning; smart buildings and cities; intelligent driving; data science; smart healthcare and healing environments; ambient persuasion; and new and emerging themes.